When to consider thyroid dysfunction in the neurology clinic. Issue 3 (15th May 2009) - Mistry, N; Wass, J; Turner, M R
Abstract : There are many neurological manifestations of thyroid disease, and thyroid function has taken its place in the "routine bloods" of neurology practice. However, although conditions such as carpal tunnel syndrome prompt thyroid testing despite any clear evidence for this approach, other symptoms of potential significance in terms of thyroid disease may be overlooked in the busy general neurology clinic, or abnormal thyroid tests may be assumed to be incidental. Psychiatric disorders, loss of consciousness, movement disorders and weakness may all be manifestations of primary thyroid disease. This is a symptom-based review where we will consider the evidence (or lack of it) for the association of various neurological problems with thyroid dysfunction, and also the pitfalls in interpretation of the biochemical tests.